Людина в інформаційній економіці - Лінькова, Олена Юріївна (НТУ "ХПІ", 2009)
Проаналізовані наслідки формування інформаційного суспільства. Розкрито зміст інформаційних реформ. Виокремлено суперечності сучасного суспільства. Запропоновані напрямки щодо їх подолання на основі механізму управління творчістю. Визначені умови всебічного розвитку особистості. Зазначено значущу роль інформації та людини для розвитку економіки та суспільства.

Consequences of the forming of information society have been analyzed. The contents of information reforms have been discovered. Contradictions of the modern society have been selected. Directions of their overcoming on the base of the mechanism of management by creation have been offered. Conditions of the comprehensive development of a personality have been defined. The meaningful role of information and a human for the development of economics and society has been defined
Keywords: механізм управління творчістю; постіндустріальне суспільство; інформаційна економіка; людська особистість; інтелектуальний потенціал